Antidiabetic Function of Lactobacillus fermentum MF423-Fermented Rice Bran and Its Effect on Gut Microbiota Structure in Type 2 Diabetic Mice - Ai, Xiaojuan; Wu, Cuiling; Yin, Tingting; Zhur, Olena; Liu, Congling; Yan, Xiaotao; Yi, CuiPing; Liu, Dan; Xiao, Linhu; Li, Wenkai; Xie, Binbin; He, Hailun (Frontiers in Microbiology, 2021)
Rice bran is an industrial byproduct that exerts several bioactivities despite its limited bioavailability. In this study, rice bran fermented with Lactobacillus fermentum MF423 (FLRB) had enhanced antidiabetic effects both in vitro and in vivo. FLRB could increase glucose consumption and decrease lipid accumulation in insulin resistant HepG2 cells. Eight weeks of FLRB treatment significantly reduced the levels of blood glucose and lipids and elevated antioxidant activity in type 2 diabetic mellitus (T2DM) mice. H&E staining revealed alleviation of overt lesions in the livers of FLRB-treated mice. Moreover, high-throughput sequencing showed notable variation in the composition of gut microbiota in FLRB-treated mice, especially for short-chain fatty acids (SCFAs)-producing bacteria such as Dubosiella and Lactobacillus. In conclusion, our results suggested that rice bran fermentation products can modulate the intestinal microbiota and improve T2DM-related biochemical abnormalities, so they can be applied as potential probiotics or dietary supplements.